Faktor Kerentanan Food Fraud dan Mitigasinya : Studi Kasus Pada Produsen Susu Bubuk di Indonesia - A. Fitrawanti; R. Dewanti-Hariyadi; N. Wulandari (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2021)
Food fraud is one of the risks in the supply chain globalization. A complex and long supply chain withdifferent locations, cultures, business ethics, policies and surveillance systems are the contributing factorsto food fraud. This study aims to identify food fraud vulnerability factors in milk powder producers. Itwas conducted in two companies which uses powder and liquid milk as the raw materials which istypical in Indonesian powdered milk industry. The study steps consist of respondents determination,data collection and analysis, formulating mitigation strategies. The respondents were company’s headof departments and a government officer of the National Agency for Drug and Food. Data collectionand analysis were carried out with the Safe Supply Affordable Food Everywhere (SSAFE) tool, whilemitigation strategies was formulated through Focus Group Discussion. The results show that vulnerabilityto food fraud rooted from the opportunity factor, namely the easiness and availability of technologyto commit fraud, motivational factor namely the level of corruption and regulatory differences thataffect prices, control measures factors due to lack of supervision, employee integrity tests and preventionguidelines. Internally improving control measures within the company and guideline prevention fromthe government were mitigation measures to be done.